A Qualitative Description of Millennial Nurse Administrators' Perspectives on Leadership and their Practice Environment - John Ian Lamasan; Ryan Michael Oducado (Indonesian Nursing Journal of Education and Clinic, 2018)
Introduction: Millennial nurses are beginning to accept leadership roles and will soon take over governance in the nursing profession and healthcare industry. This study aimed to describe the perspectives on leadership and their practice environment of millennial nurse administrators working in tertiary hospitals in Iloilo City, Philippines. Methods: Eight (8) millennial nurse administrators were purposively chosen. Through a qualitative descriptive inquiry by Sandelowski (2000), data were gathered using semi-structured interviews and analyzed employing qualitative content analysis. Results: Twelve (12) meaningful categories were derived directly from the interview transcripts. Millennial nurse administrators perceive leadership by way of (1) directing, (2) guiding, (3) empowering and (4) modeling to staff. They viewed their practice environment as (5) having a harmonious relationship while (6) maintaining professional relationship among the healthcare team members, (7) upholding standards and (8) ensuring client satisfaction as a measure of quality care. Millennial nurse administrators shared feelings of being (9) overwhelmed at the start yet (10) fulfilling in the end. Lastly, they had challenges in (11) dealing with older staff and in (12) assuming the full responsibility and accountability of their unit. Conclusions: Considering the complexities in the healthcare profession, millennial nurse administrators cope with the responsibilities brought by their position as major key players to ensure that unit operations abide with practice standards. Millennial nurse administrators must be provided with understanding, support, and mentoring, to enhance their leadership competencies as they progress into higher leadership positions.
Keywords: 330; leadership; management; millennial nurses; Generation Y